Gastro-retentive Floating Tablets For Leprosy: Current Trends and Challenges - Mahale Rushikesh,; Deore Sapana,; Jadhav Shivraj,; Mahajan Sunil, (Asian Journal of Pharmaceutical Research and Development, 2025)
Leprosy, also known as Hansen’s disease, is a chronic infectious condition caused by Mycobacterium leprae, primarily affecting the skin, peripheral nerves, mucosa of the upper respiratory tract, and eyes. Despite its ancient origin and significant social impact, leprosy remains a public health concern in several endemic regions. This review explores the historical background, pathogenesis, and current World Health Organization (WHO)-recommended diagnostic and therapeutic strategies for leprosy. Emphasis is placed on multidrug therapy MDT), which includes dapsone, rifampicin, and clofazimine, as the cornerstone of treatment. The article further examines the role of gastroretentive drug delivery systems (GRDDS) in optimizing the pharmacokinetics and therapeutic efficacy of anti-leprosy agents. GRDDS are innovative oral formulations designed to prolong gastric residence time, thereby enhancing drug absorption in the upper gastrointestinal tract. Floating drug delivery systems (FDDS), a subclass of GRDDS, are particularly suitable for drugs like rifampicin, which exhibit narrow absorption windows or instability in the intestinal environment.The review discusses the mechanisms of gastroretention, including low-density floating, mucoadhesion, swelling, and high-density systems. Special focus is given to floating tablet technologies, their formulation strategies for leprosy management, and the various types of FDDS such as effervescent and non-effervescent systems. Key challenges in the development of floating tablets including formulation stability, drug loading efficiency, in vivo buoyancy, and patient variability are also outlined. Finally, the review highlights ongoing advancements and potential future directions in the integration of GRDDS with anti-leprosy therapy.